Evaluasi Pendampingan Branding berbasis Platform Digital bagi UMKM se-Malang Raya - Tubagus Mohamad Akhriza; Evy Sophia; Weda Adistianaya Dewa (LPPM STIKI MALANG, 2022)
IAII-Jatim has organized a digital platform-based business branding assistance activity for MSMEs in Malang Raya. The material provided is the concept and design of logos, packaging and ad copy which are elements of a brand. The evaluation of the results of the assistance has been carried out, and a report on this activity and the results of the evaluation is presented in this article. One of the evaluation methods applied is the clustering of business units and their responses to the materials and activities of this assistance. Using K-means, four clusters were obtained which explained that there are some business units that do not want to use digital platforms for branding, some units that have used several social media for branding but do not want to apply the proposed branding element design, while other units want to apply the proposed design on the digital platform they have been using so far.